the Review literature: The effect of prices and income on consumer choice and consumption in Islam: substitusi effect and income consumption in Islam - AMIN, AL -; Astuti, Tifany Y; Anggreni, Melisa; Khairani, Zelfia; Nasriandani, Elvi; Alfiona, Fifa; Putri, Anne; Asyari, Asyari (ADPEBI, 2022)
The change in the quantity demanded caused by a change in price occurs through two effects that are complementary to each other, which are called the substitution effect and the income effect , these effects also affect theory. behavior consumer in islam and based on law Islam on basically different with theory conventional. Difference this concerns score core in lower theory, motive and destination consumption, technique choice and allocation budget consumption. The method used in this study is literature review, with various sources of journal literature in the last five years. Based on the results of the reviewed articles that can explain how changes in relative prices affect consumer choices. And when choosing a product, consumers will consider its price as well as the price of alternative products from the cross-price elasticity of demand. And in Islam, the level of consumption of these goods is usually termed goods that are daruriyat, tahsiniyat, and hajiyat.